The complete mitochondrial genome and phylogenetic analysis of Yanglong yak (Bos grunniens). Issue 4 (3rd April 2021) - Guo, Shaoke; Wu, Xiaoyun; Song, Rende; Za, Xita; Zhao, Qingzhang; Li, Jiye; Ma, Haiqing; Wu, Fude; Liang, Chunnian; Pei, Jie; Guo, Xian
Abstract: In this study, we assembled the complete mitochondrial genome of Yanglong yak ( Bos grunniens ) from Illumina sequencing reads. The mitochondrial genome is 16, 323 bp long with an A + T-biased nucleotide composition, and encodes 13 protein-coding, 22 tRNA, and two rRNA genes along with a noncoding control region. In addition, its gene order is identical to those of the previously published mitochondrial genomes of its congeners. Phylogenetic analysis indicates that this breed is closely related to Datong yak, Pamir yak, Tianjun yak, polled yak, Seron yak, Sunnan yak, a series of Domestic Yak and wild yak, followed by Jinchuan yak and Gannan yak, and slightly far away from Bison and Bos taurus .